Application Of New Public Management (NPM) In Indonesia In The Field Of Transportation (Case In Bandar Lampung) - Prawira Yudha Pratama; Rita Kalalinggi (Journal of Governance and Public Policy, 2019)
This paper explains the results of studies and information on the application of New Public Management (NPM) in Indonesia in the field of transportation (the case in Bandar Lampung). Finding New Public Management is applied not only in countries with high levels of prosperity but also applied in countries with levels similar to the conditions in Indonesia. Apart from deficiencies in the implementation of regional autonomy, the application of NPM in the management of local government in Indonesia has a positive impact on several matters, more trapped performance of accountability of government institutions and moratorium and early retirement policies for civil servants who do not qualify as an effort to improve efficiency and the productivity performance of local governments, which in turn will improve the quality of public services. The creation of partnerships between the public and private sectors or public-private partnership (PPP) has now become a standard concept in the local government environment. The concept of Trans BRT, Bandar Lampung BRT as the first in Indonesia to operate without government subsidies is a new thing in Indonesia. The strong desire and passion of the City of Bandar Lampung and transportation stakeholders in Bandar Lampung to create convenient urban transportation.